Effect of calcination temperature on phase and morphology of sol-gel derived PZTN powders - Sangsubun C. (2014)
Niobium doped PZT (PZTN) powder was prepared by a triol-sol-gel method from a mixture of lead (II) acetate trihydrate, 1,1,1 -tris (hydroxymethyl), acetylacetone, titanium (IV) isopropoxide, zirconium (IV) propoxide and niobium (V) ethoxide and calcined at temperature ranging from 300-600°C for 2 h and 600°C for 4 h with a heating/cooling rate of 5°C/min. Thermal characteristics of the PZTN powders were studied using thermogravimetric/ differential thermal analyses (TG/DTA). Phase formation in the powder was determined using X-ray diffraction analysis (XRD). Morphology of the PZTN powder was investigated by a scanning electron microscopy (SEM) and transmission electron microscopy (TEM). High purity perovskite structure of PZTN powder with a rhombohedral structure and a crystallite size ∼38 nm was obtained at the temperature of 600°C for 4 h dwell time. Well separated particles with uniform particle size distribution within 10-50 nm were also observed by TEM. © 2008 Trans Tech Publications, Switzerland.